9(8y-6)-(4y+8)=

Simple and best practice solution for 9(8y-6)-(4y+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(8y-6)-(4y+8)= equation:


Simplifying
9(8y + -6) + -1(4y + 8) = 0

Reorder the terms:
9(-6 + 8y) + -1(4y + 8) = 0
(-6 * 9 + 8y * 9) + -1(4y + 8) = 0
(-54 + 72y) + -1(4y + 8) = 0

Reorder the terms:
-54 + 72y + -1(8 + 4y) = 0
-54 + 72y + (8 * -1 + 4y * -1) = 0
-54 + 72y + (-8 + -4y) = 0

Reorder the terms:
-54 + -8 + 72y + -4y = 0

Combine like terms: -54 + -8 = -62
-62 + 72y + -4y = 0

Combine like terms: 72y + -4y = 68y
-62 + 68y = 0

Solving
-62 + 68y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '62' to each side of the equation.
-62 + 62 + 68y = 0 + 62

Combine like terms: -62 + 62 = 0
0 + 68y = 0 + 62
68y = 0 + 62

Combine like terms: 0 + 62 = 62
68y = 62

Divide each side by '68'.
y = 0.9117647059

Simplifying
y = 0.9117647059

See similar equations:

| -s^2+10s=0 | | 24-22=-4(1-6) | | 11n+22n= | | (-4xy)*(3y)= | | 45*-27= | | [-19+(-7)]+[-18+20]= | | 45x-27= | | y-12=6X+120 | | (1/4)j=-16 | | 2x^4+3x^2=1 | | 12r-20=2r | | 36y^2-108+81=0 | | 1/2x=3/10 | | -8y+6=-5+4y | | 2*(x-17)=-x/2 | | 32y^2+18= | | 54p^2+45p-54=0 | | 35m+25m=609 | | 16x^2+31x=14 | | 6x+17=175 | | 6x+17=44 | | 48x-3x^3=0 | | 5/3+2/3x=31/15+8/5x+1/5 | | 3/2x-1/2x-4-7=-13-1 | | 163x=2/y | | 7*(x-6)=21 | | 5-2x=7x+18 | | 112=7x+(-4x-17) | | 7(3n+4)=9(8n+8)+1 | | 3m^2+5m-12=0 | | 2xy^4+5xy^4-7x^4y= | | 11/3=-4p+1/3p |

Equations solver categories